Utilisation of E-Library Resources for Learning among University of Ilorin Arabic Students, Nigeria - ABDULLAHI, Musa Siddiq; SALISU, Musa; SHITTU, Hamzat Atunnise (Ilorin Journal of Education, 2024)
Electronic libraries or virtual libraries which are popularly known as E-library began to emerge in the 1970s. Recently, it has risen to internet stage, with it, the web development and web-based resources and access tools which include data bases. This study examined the utilisation of e-library among Arabic students in University of Ilorin, Nigeria. The population for the study comprised all Arabic students in University of Ilorin, Nigeria. Ninety-one Arabic students who were users of the e-library were sampled using a clustered sampling procedure. Researchers’ developed questionnaire was used to gather data and the data collected were analysed with the percentage, mean, and t-test at 0.05 alpha level. The findings revealed that the internet, e-journals, e-library research, the World Wide Web, e-books, e-theses, CD-ROM, reference materials and bibliographic database were the e-library resources utilized among Arabic students in University of Ilorin. No significant difference existed in the utilisation of e-library among Arabic students based on gender and faculties except educational level. It was recommended that there should be a comprehensive education programme for users of the e-library in order to prepare them with the prerequisite knowledge and skills on information technology, more computer systems should be provided to accommodate more users at a time.